Intraductal tubulopapillary neoplasm of the bile duct: A case report and review of the published work. Issue 7 (2nd November 2015) - Nakagawa, Takashi; Arisaka, Yoshifumi; Ajiki, Tetsuo; Fujikura, Kohei; Masuda, Atsuhiro; Takenaka, Mamoru; Shiomi, Hideyuki; Okabe, Yoshihiro; Fukumoto, Takumi; Ku, Yonson; Azuma, Takeshi; Zen, Yoh
Abstract : Recent studies have suggested that a peculiar tumor mimicking intraductal tubulopapillary neoplasms (ITPN) of the pancreas can develop in the bile duct. Here, we present a similar case and review the published work on the newly proposed biliary neoplasm. A 68‐year‐old woman was referred to us for further evaluation of a liver mass. On imaging, the tumor was 40 mm in size and intraductal in location, and was enhanced slightly on the contrast‐enhanced computed tomography. No mucin overproduction was found. She underwent right hepatectomy for suspected intraductal papillary neoplasm of the bile duct. The tumor histologically consisted of the biliary‐type epithelium arranged in a tubular architecture within the dilated bile duct. Tumor cells had features of high‐grade dysplasia but no stroma invasion. No expressions of MUC2 and MUC5AC were noted. On molecular studies, KRAS and GNAS appeared to be wild‐type genotypes. These features were in keeping with ITPN. In the published work review, "biliary ITPN" described in four manuscripts were characterized by predominantly intrahepatic/hilar in location, histological tubular architecture, negative expressions of MUC2 and MUC5AC, and uncommon alterations of KRAS, GNAS and BRAF . Although invasive malignancy was present in 71%, the outcome was favorable with the 5‐year survival expected to be approximately 90%. Biliary ITPN are supposedly uncommon, but a greater awareness of this condition may give more chance to diagnose the underrecognized neoplasm.